Is ChatGPT Building or Destroying Education? Perception of University Students in Tanzania - George Matto (Noyam Journals, 2024)
Since its launch, ChatGPT has gained popularity and is widely used by university students. The tool has both positive and negative effects on students' education. In other words, it contributes to either the building or destruction of education. This study was conducted to ascertain university students' perceptions of whether ChatGPT is building or destroying their education. A cross-sectional research design was employed, in which data were collected from 200 randomly selected students from two Tanzanian Universities. The collected data was analysed using SPSS, in which frequencies, means, and standard deviation (SD) facilitated descriptions of various aspects of the study. Results showed that the majority of university students in the study area (around 81.5%) were using ChatGPT for a variety of reasons, including helping them prepare for exams, undertaking assignments, and writing research proposals and reports. Although there are negative impacts, such as reducing academic integrity and diminishing critical thinking, it was established that if ChatGPT is used cleverly, it stands to build rather than destroy education. Thus, this study recommends that universities should consider formulating and operationalizing respective policies and guidelines, as detailed further in the document. The study, therefore, delivers more clarity on the nexus between the use of ChatGPT and University education endeavours.